New thyristor-based hybrid DC circuit breaker with reverse injection of resonant current - Cha, Jee Yoon; Lee, Eui Jae; Han, Byeol; Lee, Kyo Beum; Han, Byung Moon (Journal of Power Electronics, 2022)
This paper proposes a thyristor-based hybrid DC circuit breaker (HDCCB), which is composed of a fast mechanical circuit breaker and an LC resonant circuit with thyristor switches. The proposed HDCCB provides a zero-crossing point for fault current by injecting a resonant current in the reverse direction of the fault current. The proposed HDCCB has a low conduction loss in normal operation using a mechanical circuit breaker, and it offers the advantages of low cost, high reliability, and large capacity using thyristor switches instead of IGBT switches. It also has the design flexibility to adjust the magnitude of the injection current depending on the fault current level. A bidirectional HDCCB is also proposed by adding several components to the developed unidirectional HDCCB, which can offer compact system size and low system cost. Design considerations of the proposed structure are discussed. The validity of the proposed HDCCB is verified by simulation and experimental results.
Keywords: Bidirectional DC circuit breaker; Circuit-breakers; Current injection methods; D.C Circuit; DC circuit breaker; DC circuits; Hybrid DC circuit breaker; Reverse current injection method; Reverse currents; Bidirectional DC circuit breaker; DC circuit breaker; Hybrid DC circuit breaker; Reverse current injection method